Pengaruh IPM dan Kemandirian Keuangan Terhadap Financial Sustainability Pemerintah Kota Yogyakarta - Ernawati, Ernawati; Putra Prasetya, Bangun (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Islam Majapahit, 2024)
This research aims to examine the factors that influence Financial Sustainability in the Yogyakarta City Government. The factors chosen from a financial perspective are financial independence and a social aspect, namely the HDI or Human Development Index of the Yogyakarta City Government. The research sample used was the HDI and Financial Independence of the Yogyakarta City Government in 2014 - 2022. The data analysis method used was SPSS version 27. Based on the research results, it can be partially concluded that the HDI (Human Development Index) has no effect on Financial Sustainability. Meanwhile, Financial Independence partially influences Financial Sustainability. Simultaneously, the HDI (Community Development Index) and Financial Independence have a significant effect on the Financial Sustainability of the Yogyakarta City Government.